Aides logicielles à la lecture de textes documentaires scientifiques - Jacques Crinon; Denis Legros; Brigitte Marin; Patrick Avel (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
A series of studies have allowed to elaborate a hypertext computer system that helps students to understand scientific texts and to evaluate the effect of two kinds of explanatory notes. The first ones are based on the "text base", the other ones are based on the "situation model". They are presented on a sheet of paper and on a computer screen in different situations where reading aims at training and where reading is in order to create and solve a scientific problem. The results show that the hypertext presentation helps the students to build a more coherent representation of the situation evoked by the text. This particularly happens when the reader gets explanatory notes in connection with the "situation model" that provides him clear knowledge in connection with the information of the text, that allows him to fill in the "semantic blanks" of the text.